Management of waste from the pruning of urban greenery. Experiences in São Paulo, Brazil - Tomás Queiroz Ferreira Barata; Cyntia Santos Malaguti de Sousa; Caio Dutra Profirio de Souza; Debora Klingenberg (Agathón)
The waste management of urban greenery is directly related to the sustainability of cities. Architects, designers, managers, and entrepreneurs have used woody residues creatively, in innovative business models, focusing on the transition to a circular economy. This article presents a systemic analysis of experiences on the theme, with an emphasis on the use of woody residues, from the design perspective, taking the State of São Paulo, Brazil, as the locus of investigation. The research covers: consolidation of the theoretical knowledge, bibliographic review on guidelines, best practices and production flow models, and the diagnosis of four local initiatives. The results demonstrate the relevant role of design as an inducer of new business models, as well as the importance of universities, in knowledge dissemination, technology transfer, and new initiatives proposals, with multiplier effects.